Identifikasi Bakteri dan Kapang dalam Proses Pembuatan Bioetanol Menggunakan Campuran Feses Ayam Broiler dan Tandan Kosong Kelapa Sawit - Assidiqi, Hadi Yusril; Marlina, Eulis Tanti; Harlia, Ellin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Every year, waste from the livestock and agricultural sectors increases, including broiler chicken feces and empty fruit bunches (EFB). EFB contains 32.57% cellulose, 27.70% hemicellulose, and 26.49%. The presence of lignin in lignocellulose is an obstacle, so it is necessary to degrade it with the help of cellulolytic bacteria in broiler chicken feces through the decomposition stages. This research aims to identify macroscopically and microscopically the bacteria and mold in making bioethanol using a mixture of broiler chicken feces and EFB. This research used an exploratory method, the data obtained was then analyzed descriptively with 3 treatments and 6 replications for each treatment, namely P1 (60% broiler chicken feces : 40% EFB), P2 (70% broiler chicken faces : 30% EFB), and P3 (80% broiler chicken feces : 20% EFB) which were observed on days 1, 7, and 14 in the decomposition stage. The highest average colony of bacteria was 199.83 x 108 CFU/gram and mold was 106.17 x 104 CFU/gram. The Bacillus group was the most commonly found bacterial group, with 11 isolates from 27 isolates. Aspergillus, Trichoderma, and Penicillium are the mold groups that play a role in this research.